Same-Sex and Different-Sex Parent Households and Child Health Outcomes: Findings from the National Survey of Children's Health. Issue 3 (April 2016) - Bos, Henny M. W.; Knox, Justin R.; van Rijn-van Gelderen, Loes; Gartrell, Nanette K.
ABSTRACT: Objective: Using the 2011–2012 National Survey of Children's Health data set, we compared spouse/partner relationships and parent-child relationships (family relationships), parenting stress, and children's general health, emotional difficulties, coping behavior, and learning behavior (child outcomes) in households of same-sex (female) versus different-sex continuously coupled parents with biological offspring. We assessed whether associations among family relationships, parenting stress, and child outcomes were different in the 2 household types. Methods: Parental and child characteristics were matched for 95 female same-sex parent and 95 different-sex parent households with children 6 to 17 years old. One parent per household was interviewed by telephone. Multivariate analyses of variance and multiple linear regressions were conducted. Results: No differences were observed between household types on family relationships or any child outcomes. Same-sex parent households scored higher on parenting stress (95% confidence interval = 2.03–2.30) than different-sex parent households (95% confidence interval = 1.76–2.03), p = .006. No significant interactions between household type and family relationships or household type and parenting stress were found for any child outcomes. Conclusion: Children with female same-sex parents and different-sex parents demonstrated no differences in outcomes, despite female same-sex parents reporting more parenting stress. Future studies may reveal the sources of this parenting stress.